2018
DOI: 10.1371/journal.pbio.2004328
|View full text |Cite
|
Sign up to set email alerts
|

The Plasmodium falciparum transcriptome in severe malaria reveals altered expression of genes involved in important processes including surface antigen–encoding var genes

Abstract: Within the human host, the malaria parasite Plasmodium falciparum is exposed to multiple selection pressures. The host environment changes dramatically in severe malaria, but the extent to which the parasite responds to—or is selected by—this environment remains unclear. From previous studies, the parasites that cause severe malaria appear to increase expression of a restricted but poorly defined subset of the PfEMP1 variant, surface antigens. PfEMP1s are major targets of protective immunity. Here, we used RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
187
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(206 citation statements)
references
References 120 publications
(220 reference statements)
15
187
4
Order By: Relevance
“…Previous studies have suggested that malaria parasites may exhibit multiple distinct metabolic phenotypes in vivo, including starvation states and normal glycolytic growth states, with variation in the expression of glycolysis, TCA cycle, and fatty acid metabolism genes (48)(49)(50). While these studies have not been conclusive in terms of which host environments trigger such variation in parasite metabolic states, in agreement with these previous studies, the present study also finds evidence of variation in TCA and fatty acid metabolism genes in vivo.…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies have suggested that malaria parasites may exhibit multiple distinct metabolic phenotypes in vivo, including starvation states and normal glycolytic growth states, with variation in the expression of glycolysis, TCA cycle, and fatty acid metabolism genes (48)(49)(50). While these studies have not been conclusive in terms of which host environments trigger such variation in parasite metabolic states, in agreement with these previous studies, the present study also finds evidence of variation in TCA and fatty acid metabolism genes in vivo.…”
Section: Discussionsupporting
confidence: 88%
“…Specifically, it was proposed that the parasite cellular physiology could be (at least in part) controlled by fine-tuned transcriptional profiles of genes regulating active growth via glycolysis and/or alternative carbon source metabolism as well as other environmental stress responses. Distinct global transcriptional variations can also be associated with disease-related phenotypes such as malaria infection during pregnancy 36 , 37 and severe malaria with cerebral complications 38 , 39 . While pregnancy-associated malaria seems mainly associated with upregulation of genes encoding specific surface antigens (such as var and phist genes), the severe infections involve parasites with more complex transcriptional changes in processes such as energy metabolism, biosynthesis, protein synthesis and folding, and cytoadhesion.…”
Section: Discussionmentioning
confidence: 99%
“…Immune evasion strategies employed by P. falciparum have also been reviewed elsewhere . Other recent reviews explore the extent of genetic variation and gene expression in malaria parasites and how Plasmodium genomes and transcriptomes are now readily able to be sequenced and analysed . These technological advances are facilitating our ability to investigate human‐parasite interactions and led to the finding that vaccine‐induced antimalarial immunity is strain‐specific …”
Section: Overview Of Malariamentioning
confidence: 99%
“…15 Other recent reviews explore the extent of genetic variation and gene expression in malaria parasites 16 and how Plasmodium genomes and transcriptomes are now readily able to be sequenced and analysed. 17,18 These technological advances are facilitating our ability to investigate human-parasite interactions and led to the finding that vaccine-induced antimalarial immunity is strain-specific. 19 Understanding immune effector mechanisms in malaria-exposed individuals has been approached from two complementary perspectives: identifying mediators of immune-induced pathology and distinguishing them from those that confer protection.…”
Section: O M M I S S I O N E D R E V I E W a R T I C L Ementioning
confidence: 99%